Factors Affecting Customer’s Bank Selection Decision: A Study on Commercial Bank in Jimma Town Ethiopia - Serkalem Tesfaye; Abera, Mekuanint; Tadele Mengesha (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The objective of this study was to examine factors affecting customers’ bank selection decision. The study employs cross sectional survey design and mainly conducted based on data collected through questionnaires and interviews. The Sample size of the study was 384. The collected data were analyzed through SPSS version (20). The descriptive and inferential statistical tools such as mean, percentage, ANOVA, correlation and multiple linear regressions were used to analyze collected data. The regression model summary shows that the all independent variables explain 53.5 % variability on bank selection decision and model explains significant variability of customer bank selection intention by five decision variables. The Findings revealed that; out of five factors ,four factors such that: technology factors, service quality factors, bank image and reputation factors, and convenience factors have significant and positive relation with bank selection decision while financial factor has insignificant relation with bank selection decision. As customers place more emphasis on factors like convenience, service quality, technology and bank image and reputation, Such factors better to be considered seriously by banks in their marketing strategies which help them to attract new as well as retain the existing customers.